Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.